Failure analysis of a submersible pump shaft - Jayabalan, J. Kulasegaran (2007)
Submersible pump are widely used in a wastewater pumping station and treatment plants, to transfer sewage from a sump or wet well to other parts of the processes. Usually when a centrifugal pump is operating at its best efficiency point (BEP), the bending forces are evenly distributed around the impeller. If the pump discharge is throttled from this best efficiency point, then the fluid velocity is changed and causes the hydraulic radial imbalances load to increase at the impeller of the pump. Therefore, the shaft of the submersible pump is subjected to cyclic stresses due to this hydraulic radial imbalance loading and torsional load. This thesis mainly focuses on the distribution of stresses on the critical area of the shaft due to the imbalance loads and to determine the causes of failure to the shaft. Methodology used to carry out th e study are mainly through analytical calculation (static & fatigue) and 3D analysis (Finite element analysis & fatigue life cycle analysis). Results from both the analytical and 3D analysis shows that the pump shaft has been designed for infinite life as the fatigue life cycle is in the region of 1010 to 1012 cycles at the critical area of the shaft. Since the shaft has been designed for infinite life, the other factors such as stress corrosion cracking, pitting, cavitations and imperfection during manufacturing are suspected to be the possibilities of main contributors to the failure of the shaft, mainly due to fatigue under cyclic loading when it is in operation.